Detection of Pentastomida on Crab-Eating Frog (Fejervarya cancrivora) in Surabaya and Sidoarjo Areas - Gilang Maulana Putra; Emmanuel Djoko Poetranto; Fedik Abdul Rantam (Universitas Airlangga, 2020)
This research was conducted to detect the presence of Pentastomida on Crab-eating Frog (Fejervarya cancrivora) in Surabaya and Sidoarjo areas. A total of 50 samples were taken in three different time and the identification was conducted in Laboratory of Parasitology, Universitas Airlangga by Semichen-Acetic Carmine staining method. Pentastomida that found in the body of Crab-eating Frog (Fejervarya cancrivora) was belong to Maxillopoda class which is included in Crustacea subphylum were matched by macroscopic and microscopic taxonomy and observation. The result of this research showed that there found Pentastomida on Crab-eating Frog collected Surabaya and Sidoarjo areas, East Java.